Pengaruh Sarana Prasarana Bengkel Las dan Motivasi Belajar Praktik terhadap Hasil Belajar Siswa pada Mata Pelajaran Shielded Metal Arc Welding (SMAW) Kelas XI Teknik Pengelasan SMK Negeri 1 Sumatera Barat - Manik, Yeremia Owen; Rahim, Bulkia; Irzal, Irzal; Indrawan, Eko (Lembaga Yasin AlSys, 2025)
This study is motivated by the crucial role of practical facilities and student learning motivation in supporting learning outcomes, particularly in SMAW welding practice instruction at vocational high schools. The objective of this research is to determine the influence of welding workshop facilities and practical learning motivation on the learning outcomes of Grade XI Welding Engineering students at SMK Negeri 1 West Sumatra. The study uses a quantitative method with a correlational approach, involving 25 students as the sample. Data were collected through questionnaires, documentation, and observation, and analyzed using simple and multiple linear regression. The results show that: (1) welding workshop facilities significantly affect student learning outcomes, with a t value of 2.762 and the regression equation Y = 57.235 + 0.328X₁; (2) practical learning motivation also significantly affects learning outcomes, with a t value of 3.095 and the regression equation Y = 55.981 + 0.338X₂; (3) simultaneously, both variables have a positive and significant effect on student learning outcomes, with a coefficient of determination R² = 0.315 and the regression equation Y = 52.831 + 0.812X₁ + 1.451X₂. These findings confirm that the availability of adequate practice facilities and high practical learning motivation together can improve student learning outcomes in SMAW welding subjects. The implication is that schools need to ensure the provision of appropriate practice facilities and foster student motivation through contextual and participatory learning strategies.